The Word and the Law. By Milner S. Ball. Chicago: University of Chicago Press1995 (reprint ed.). Pp. 216. Paper. $16.00. ISBN: 0-226-03627-8. - Hartigan, Emily Albrink Fowler (Journal of law and religion, 2001)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0748081400007827/resource/name/firstPage-S0748081400007827a.jpg